Formulations of Melia azedarach to control diabrotica speciosa (germar) (coleoptera: chrysomelidae) larvae in corn and plant enhancement - Souza, B. H. S. [UNESP]; Costa, E. N. [UNESP]; Forim, M. R.; Costa, E. S.; Boica Junior, A. L. [UNESP] (Entomological Soc Brasil, 2015)
We evaluated oil and powder formulations of Melia azedarach for controlling larvae of Diabrotica speciosa (Germar) in corn and plant enhancement. Five concentrations of each formulation were evaluated and compared to fipronil (negative control) and distilled water (positive control). After treatment, the number of surviving insects (larvae, pupae, and adults), the adult body weight, the sex ratio, and the longevity were recorded, while the height, dry weight of aerial part and roots, and number of leaves of plants were measured. The oil formulation at 4.0 mL reduced the larvae population of D. speciosa similarly to the insecticide fipronil, which resulted in greater height, dry weight of the root system, and number of leaves. Powder formulation at concentrations of 40, 80, and 160 mg caused larval mortality above 80%; however, these concentrations did not prevent reduction of plant height and dry weight of aerial part. Further studies assessing the residual period of M. azedarach control against D. speciosa larvae and its phytotoxicity, which are common traits associated with azadirachtin application, are necessary to subsidize the next steps of this alternative control strategy.
Keywords: Bean leaf beetle; Botanical insecticide; Corn rootworm; Sustainable pest management